Peritoneal dialysis in patients over 65 tears. A Good therapeutic choice - Gabriela González; Miguel Angel Nadal; Valeria Patronelli; Alejandra Copa; Abigail Gubergrit (Revista de Nefrología, Diálisis y Trasplante, 2017)
Introduction: Some authors say that patients over 65 years of age reject PD as a dialytic option. Objetives: To analyze dialytic effectiveness in patients >=65 years old on PD. Material and Methods: From 1/2011 to 1/2015, 27 patients over 65 years were studied. 19 males and 8 females, age 74.6 years (65-87), period of time on PD : 42.9 (5-55) months. 14 CAPD and 13 APD. Clinical indicators, peritonitis rate, total dropout because of peritonitis and death, nursing requirements and quality of life. Results: 9 (33%) required nursing. 13 had peritonitis (48%), 7 had only one episode that did not cause morbility and 6 dropped out from PD due to peritonitis. Peritonitis episodes 1/50 mp. 11 patients dropped out (40.7%), 4 because of peritonitis. 2 patients died due to peritonitis, 4 were transferred to HD and 1 recovered renal function. Clinical indicators: Kt/v>=1.7, 85% and 78%; Serum P p<= 5.5 mg/dl 85% CAPD and 70% APD respectively; calcemia >= 8.5 mg/dl 87%, HB<= 10g/dl 81% PTH between 150 and 400 pg/ml 67 % and plasma albumin >= 3.5 g/dl 78% for both therapies. Technique survival: 62%, 55%, 40%, and 25% in 12, 24, 36 and 48 months respectively. Longer training time, lesser skill, more respiratory infections and cardiovascular complications were observed. Conclusions: ?Third age patients? demand a multidisciplinary treatment. PD is an advantageous therapy in patients suffering from cardiovascular diseases and difficulties to achieve a vascular access. Complications associated to PD do not differ from those applied to younger patients.